Rancang Bangun Sistem Penyiraman Tanaman Tomat Menggunakan Modul SIM 800L Berbasis Arduino Uno - Sahrul; syafaruddin Ch; Budi Darmawan (Depertment of Electrical Engineering University of Mataram, 2023)
Monitoring and watering tomato plants is still done manually. Which can damage and disrupt the growth of tomato plants. Therefore created an automated system and method for monitoring moisture request tomato plants. Arduino microcontroller-based automated system uno operated via SMS usingSIM800L as pngirim information tothe owner of the plant.To know the value of high humidity and water use Soil Moisture sensors and sensor YL-69 HC-SR04.The design is done in two stages: (1) the design of the hardware that makes the system monitoring soil moisture and water level in the tank (2) design software by making programs arduino on software integrated development environment (IDE) for the delivery of information automatically and with a method request , Based on the test results are inconclusive, the automatic monitoring system and mode request and watering can work well. The system can send information about soil moisture automatically tomato plants when soil moisture conditions are less than 50%. And the system can send information about the condition of the water levelin the tank when the <4 cm or> 4 cm. To turn on the pump can be done via SMS when soil moisture <50% and the water level in the tank> 4 cm. pumps be turned off automatically when the humidity> 80%.